Speech Acts on Nigerian Classroom Discourse: A Discourse Analysis Approach - Mariam, Anana (Elsya : Journal of English Language Studies, 2024)
A lot of speech acts have been misused by many classroom discourse participants and as a result of this, discourse exchanges are characterized by the use of disjointed and unplanned acts, interference, overloaded acts, incessant slot fillers and the like. Again, wrong applications of speech acts by the instructors are indirectly transferred to the students, who imitate them in the course of learning. Also, if the misinformed discourse participants write, their malfunctioned written speech acts may be shown in their scripts. This study therefore investigated how discourse participants apply the speech acts in technical classrooms. Data were randomly selected from lessons taught in selected technical classrooms in Lagos State, Nigeria, and the instrument for data collection was participant observation. The Speech Act Theory and Pragmatics were the theoretical frameworks for this research. One of the major findings showed that discourse participants, specifically the instructors, applied overloaded representatives that originated from retroactive interference of L1 to L2 and that resulted in the learners’ inability to understand the instructors’ teaching. I recommend that discourse participants (especially the instructors) should carefully select simple words that fit the class that they teach. They should also study their students and apply words in a direct way to assist students to comprehend easily as they learn.